The interaction of inflammatory cells in granuloma faciale - Takeshi Nakahara; Yoichi Moroi; Akari Tashiro; Hiromaro Kiryu; Masutaka Furue (PAGEPress Publications, 2010)
Granuloma faciale (GF) is a rare chronic inflammatory skin disease characterized by single or multiple reddish-brown cutaneous plaques or nodules. Although this condition is benign, its clinical course is extremely chronic with poor response to therapy. The typical histopathological features of GF include vasculitis with mixed cellular infiltration; however, its etiopathogenesis remains unknown. Here, we describe the case of a 76-year-old man with GF resistant to topical steroids. Biopsy of the lesion revealed i) dense mixed inflammatory cellular infiltrates of lymphocytes, histiocytes, neutrophils, and eosinophils, ii) mild perivascular nuclear dust and swollen endothelium of blood vessels, and iii) a narrow Grenz zone beneath the epidermis. Immunohistochemical staining demonstrated mixed cellular infiltrates intermixed with CD1a+ dendritic cells, CD68+ histiocytes, and CD4+ and CD8+ T cells.